Wood Waste Crushing Machine Training at BUMDes Banjarwaru Sejahtera - Linda Perdana Wanti; Nur Akhlis Sarihidaya Laksana; Unggul Satria Jati; Roy Aries Permana Tarigan; Bayu Aji Girawan; Radhi Ariawan; Nur Wachid Adi Prasetya; Ganjar Ndaru Ikhtiagung (Pengabdian: Jurnal Abdimas, 2024)
Background. BUMDes Banjarwaru Sejahtera is a business owned and managed by the people of Banjarwaru Village, Cilacap Regency. Some of the businesses that have been managed by BUMDes Banjarwaru Sejahtera include renting molen machines and making handicrafts such as broom handles and woven bamboo household crafts which produce an abundance of wood waste left over from the production process. So far, this wood waste has been sold to tofu craftsmen as fuel for the tofu production process. Purpose. People can use wood waste as added value by processing wood waste into handicrafts that have high economic value so that they can improve the welfare of the people of Banjarwaru village. Through this community service activity, training will be held on the use of wood waste chopping machines so that processed wood waste can be made into handicrafts such as particle boards or other handicrafts. Method. The method used is a lecture method where the community service team who are lecturers at the Cilacap State Polytechnic provide training on the use of wood waste chopping machines to members of BUMDes Banjarwaru Sejahtera and several wood craftsmen in Banjarwaru village. Results. The results of this community service activity have had a positive impact on business development at BUMDes Banjarwaru Sejahtera. Conclusion. Through this community service activity, it can be concluded that this activity has had a positive impact on the business development of BUMDes Banjarwaru Sejahtera. Apart from this, training in the use of wood waste chopping machines can also increase the competence of wood craftsmen in Banjarwaru village so they can produce more varied crafts made from wood waste.